Efeito do tamanho de covas e da profundidade de plantio sobre a produtividade da bananeira (Musa acuminata Simmonds e Sheperd) cv. ’nanicão’ - Manica, Ivo; R Condé, Alcides; Lino, José; C da C Passos, Luiz (Revista Ceres, 2025)
The effect of four hole sizes and three planting depths on banana yield were studied in Florestal, Minas Gerais, Brazil.